Dampak Liberalisasi Perdagangan dalam WTO Agreement terhadap Ketahanan Pangan Indonesia - Dewi Nurul Musjtari (Kanun Jurnal Ilmu Hukum, 2014)
Food is anything that comes from biological sources of agricultural products, agriculture, forestry, fisheries, livestock, water, and water, whether treated or untreated were intended as food or drink for human consumption. Trade liberalization in international trade provides consequences for Indonesia to follow suit. Nevertheless, the controversy lies in the widespread liberalization of regulated sectors of the WTO so that the greater power when the current that is set by the WTO has been very much. The imposition of trade liberalization is not efficient and is not appropriate to be implemented because of the benefits received by consumers is smaller than the loss received by the manufacturer, so that the total net surplus is reduced. The solution offered is to utilize the Indonesian legal political purposes as a strategy to support efforts to achieve food sovereignty can be implemented by changing the paradigm of the right to food of Indonesia is based on the concept of food security to food sovereignty paradigm as the rights of the people, the nation and the State. It is to define their own food and agricultural policies without interference from other countries. The suggestion in this paper is to be wary of any efforts to expand the scope of the WTO so as to enter areas that are difficult to be approved together. The Impact of Trade Liberalization in the WTO Agreement on Food Security Indonesia